KEKUASAAN DALAM TATARAN NEGARA DAN CIVIL SOCIETY - Faturohman, Deden (Jurnal Bestari, 2001)
In case of the relation between state and cicil society, indonesia has long experiences During pre-independent period, civil society is in premature and transition condition. However, there was positive signal towards the good civil society development. In second period, civil society has opposed to the state in a specific public sphere. The relation, firstly is in good condition. This is due to the role of thr state that still preparing for good performance in face of international sphere. In the earlier civil society has a heavy burden due to the strong role of the state. In period of New Order Regime, the state has a dominant power to civil society.